Factors Associated with Anxiety Among Nurses During The Omicron Variant COVID-19 Outbreak - Wijaya, I Made Agus Budi; Swarjana, I Ketut; Rahayuni, I Gusti Ayu Rai; Mahaputra, I Nyoman Arya (Babali Publisher, 2025)
Introduction: The COVID-19 pandemic, especially the Omicron variant, has had a broad impact on human life, especially on the economic and health aspects, including for nurses working on the front lines who are at risk of experiencing anxiety. This study aims to identify factors related to nurses' anxiety towards the Omicron variant of COVID-19. Methods: This study was conducted in Bangli Regency, Bali, Indonesia. The sampling technique used was snowball sampling with a sample size of 311 nurses. The instrument used was a questionnaire filled out by respondents via Google Forms. The analysis was univariate, bivariate (Chi-square test), and multivariate (multiple logistic regression). Results: The results of this study found that 25.7% of respondents experienced anxiety towards the Omicron variant of COVID-19. Perception and completeness of Personal Protective Equipment (PPE) were significantly related to nurses' anxiety towards the Omicron variant of COVID-19. On the contrary, the work environment and history of comorbidities did not affect anxiety. Conclusion: The factors that most influence the level of nurses' anxiety are perception and use of personal protective equipment (PPE).